EFFECT OF BORON AND PHOSPHORUS APPLICATION ON YIELD AND UPTAKE OF NUTRIENTS IN LENTIL - KUMAR, SARVESH; SINGH, VINAY; SOLANKI, V.P.S. (Annals of Agricultural Research, 2014)
A field experiment was conducted during 2006-08 at Bichpuri (Agra) to study the effect of B and P levels on the yield and nutrients uptake in lentil. The grain and straw yield of lentil increased significantly up to 4 kg B and 90 kg P2O5 /ha. The highest grain and straw yield (13.58 and 15.0 q/ha) at 4 kg B/ha was 12.6 and 20.0% higher in comparison to the yield at control. Similarly 90 kg P2O5 /ha produced highest grain and straw yield (15.47 and 18.18 g/ha), which was 46.8 and 45.0% higher compared to control. Thus, application of phosphorus gave higher yield than of boron. Application of B and P increased significantly the uptake of N, P and B in grain and straw over control. Protein content and yield of lentil grain also increased significantly with B and P application.